Analisis Kinematika Renang Gaya Dada 100 Meter Berbasis Kinovea Pada Atlet Putra Tingkat Senior Di Event Piala Walikota Surabaya Tahun 2023 - Shinta Nuriyah Anwar; Hayati Hayati; Brahmana Rangga Prastyana; Billy Emir Rizkanto (LPPM Universitas PGRI Adi Buana Surabaya, 2024)
Stroke Frequency (SF), Stroke Rate (SR), Stroke Length (SL) and Swimming Velocity (SV) in athletes are basic abilities that must be possessed to improve performance, so it is important to carry out kinematic analysis to determine the level of these basic technical abilities. This study aims to determine the kinematics of 100 m breaststroke swimming in male senior athlete participants in the 2023 Surabaya Mayor's Cup. Method: Data collection on men's 100 m breaststroke swimmers at the 2023 Surabaya Mayor's Cup event using a Sony Rx-10 Mark IV camera. After that, the data was analyzed descriptively quantitatively in the SPSS version 26 . Results: Data analysis shows the following results: SF at a distance of 25-50 m has an average of 13,9000 (strokes), at 75-100 m has an average value of 16,4000 (strokes) SL at 25-50 meters has an average -The average is 1.8400 with a frequent result of 2.08 (meters/cycle) then at 75-100 meters it has an average of 1.5480 and a frequent result of 1.47 (meters/cycle). While the SR at 25-50m has an average of 45.6100 (cycles/second) at 75-100 m has an average of 51.5950 (cycles/second). Conclusion: the results can be concluded that the most influential thing is muscle strenght, even though the SL decreases, the SR increases which causes the SV get better.